1999
DOI: 10.1111/j.1540-8167.1999.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength and Conduction Inhomogeneity in Each Atrium in Patients with Isolated Mitral Valve Disease and Atrial Fibrillation

Abstract: AF vulnerability was not confined to the left atrium immediately after defibrillation in AF patients with isolated mitral valve disease. Electrical remodeling resulting from perpetuation of AF, pathological changes extending to the right atrium, geometric changes caused by the atrial interactions occurring across the interatrial septum, or a combination of these may explain the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…Several investigators have documented that the AERP was relatively short immediately after the version of persistent AF, and this short AERP was progressively prolonged during a few days after the version. [10][11][12][13][14][15][16][17] These clinical findings matched the findings in experimental studies. On the other hand, although electrical remodeling is considered to contribute to an increase in PAF duration in clinical PAF patients, it has not been documented in clinical cases because it is practically difficult to non-invasively monitor the long-term atrial electrophysiologic properties.…”
Section: Electrical Remodeling In Clinical Paf Patientssupporting
confidence: 78%
“…Several investigators have documented that the AERP was relatively short immediately after the version of persistent AF, and this short AERP was progressively prolonged during a few days after the version. [10][11][12][13][14][15][16][17] These clinical findings matched the findings in experimental studies. On the other hand, although electrical remodeling is considered to contribute to an increase in PAF duration in clinical PAF patients, it has not been documented in clinical cases because it is practically difficult to non-invasively monitor the long-term atrial electrophysiologic properties.…”
Section: Electrical Remodeling In Clinical Paf Patientssupporting
confidence: 78%
“…Several reports, in different cardiac conditions, have shown that the risk of AF is associated with the prolongation of the P-wave, being a marker of altered atrial conduction [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In addition, preexisting alterations can provide a morphologic substrate which increases the likelihood of AF occurring in response to triggering. [6][7][8] At the molecular level, several AF-related alterations of the atrial tissue are known to be associated with activation of different signal transduction systems. [9][10][11] Signal transduction systems provide a dynamic interaction between extracellular cues and intracellular events and, thereby, these molecular pathways are involved in the regulation of gene expression, cell proliferation, hypertrophy, differentiation, migration, and cell death.…”
mentioning
confidence: 99%